2013
DOI: 10.5005/jp-journals-10001-1128
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical Outcomes in Midline Sinonasal Cancers treated with Helical Tomotherapy-based Image-guided Intensity-modulated Radiation Therapy

Abstract: Introduction Sinonasal cancers have variable biological behavior and outcomes. The physical proximity of several critical structures renders radiotherapy challenging for these cancers. Purpose To report our early experience of helical tomotherapy (HT)-based image-guided intensity-modulated radiation therapy (IMRT) in midline sinonasal cancers. Materials and methods Patients with midline sinonasal cancers were accrued on a prospective generic protocol of HT-based IMRT. HT plans were evaluated using standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Esthesioneuroblastoma had higher 2-year PFS (91.7% vs. 57.0%), OS (91.7 vs. 64.5%) compared to SNEC. The authors’ previous studies reported a 75% rate or recurrence within 2 years [14,15].…”
Section: Chemotherapy Regimens For Sinonasal Malignanciesmentioning
confidence: 96%
“…Esthesioneuroblastoma had higher 2-year PFS (91.7% vs. 57.0%), OS (91.7 vs. 64.5%) compared to SNEC. The authors’ previous studies reported a 75% rate or recurrence within 2 years [14,15].…”
Section: Chemotherapy Regimens For Sinonasal Malignanciesmentioning
confidence: 96%